Understanding perspectives of current palynology: using science with practical discourse - Tonatiuh Jiménez-Zamora; Leopoldo Galicia; David Espinosa; Irán Rivera-González; Isolda Luna-Vega (Botan‪ical Sciences, 2023)
Background: Palynological studies have contributed with topics closely linked to sustainability. However, there are still few scientific reviews that have discussed the relevance of practical applications in current palynology and its perspectives as a theoretical framework for the study of integrated landscape management. This review shows palynological contributions within agricultural model diversities in both natural and novel ecosystems. Questions: What are the current perspectives and concerns of the mature phase in palynology? What are the approaches of pollen analysis on landscape management and biodiversity conservation?Studied species: Pollen analysis and palynomorphs.Study site and dates: Global literature from current palynology.Methods: Global scientific literature using keywords, theoretical frameworks, and original articles.Results: We identified palynological perspectives for the study of sustainability based on global scientific literature: 1) ecological-evolutionary and 2) interdisciplinary research. In addition, we discussed some synergies and trade-offs between ecosystem services that were recognized through current palynology in different farming landscapes: biodiversity-based farming systems and chemical input-based farming systems. While pollen morphology and descriptive palynology can provide the basis for crop improvement, biological invasions, and the effect of deforestation on native species, more analytical approaches such as land-use indicators are necessary for sustainable management. In addition, we have included some biocultural aspects to conservation, due to a lack of practical discourse in current palynology. Conclusions: Innovative influences from current palynology are powerful approaches to integrated landscape management.